Pembangunan Sistem Informasi Perpustakaan Berbasis Web menggunakan Metode Rapid Application Development (RAD) (Studi pada : SMK Negeri 11 Malang) - Nur Aini; Satrio Agung Wicaksono; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The library which is located at SMK Negeri 11 Malang based on the observation results is still manual in providing services to library visitors who borrow books by writing a note book. Therefore a study entitled "Development of Web-Based Library Information Systems Using the Rapid Application Development (RAD) Method (Study at: SMK Negeri 11 Malang)". The Rapid Application Development (RAD) method is a method used by researchers to build a web-based library information system. Understanding Rapid Application Development (RAD) according to (Pressman, 2001) is a model of the development cycle emphasized briefly in the development of additional software, although the development process is short, does not reduce the quality of the product. The results of the development of library information systems can facilitate the admin in managing library data at any time and make it easier for users to borrow books in the library with the results of black box testing as much as 100% valid. And the results of the user acceptance test or User Acceptance Testing (UAT) conducted on 5 examiners consisting of the chairman of the library, library staff, 1 teacher, 1 staff and 1 student have the results of 84% of users agree that the School Library Information System (SIPS) Malang has fulfilled the needs of users in borrowing books in the library of SMK 11 Malang.